Single‐Source, Solvent‐Free, Room Temperature Deposition of Black γ‐CsSnI3 Films. Issue 11 (26th April 2020) - Kiyek, Vivien M.; Birkhölzer, Yorick A.; Smirnov, Yury; Ledinsky, Martin; Remes, Zdenek; Momand, Jamo; Kooi, Bart J.; Koster, Gertjan; Rijnders, Guus; Morales‐Masis, Monica
Abstract: The presence of a nonoptically active polymorph (yellow‐phase) competing with the optically active polymorph (black γ‐phase) at room temperature in cesium tin iodide (CsSnI3 ) and the susceptibility of Sn to oxidation represent two of the biggest obstacles for the exploitation of CsSnI3 in optoelectronic devices. Here room‐temperature single‐source in vacuum deposition of smooth black γ −CsSnI3 thin films is reported. This is done by fabricating a solid target by completely solvent‐free mixing of CsI and SnI2 powders and isostatic pressing. By controlled laser ablation of the solid target on an arbitrary substrate at room temperature, the formation of CsSnI3 thin films with optimal optical properties is demonstrated. The films present a bandgap of 1.32 eV, a sharp absorption edge, and near‐infrared photoluminescence emission. These properties and X‐ray diffraction of the thin films confirm the formation of the orthorhombic (B‐γ ) perovskite phase. The thermal stability of the phase is ensured by applying in situ an Al2 O3 capping layer. This work demonstrates the potential of pulsed laser deposition as a volatility‐insensitive single‐source growth technique of halide perovskites and represents a critical step forward in the development and future scalability of inorganic lead‐free halide perovskites. Abstract : High quality films of lead‐free halide perovskite cesium tin iodide (CsSnI3 ) are grown by pulsed laser deposition, a solvent‐free, single‐source in‐vacuum technique. The optically active black γ‐CsSnI3 perovskite phase is stabilized through in situ application of an amorphous, transparent capping layer.